Pengembangan Media Pembelajaran Interaktif Berbasis Website Untuk Meningkatkan Keterampilan Penalaran Matematis - Nurimani; Zaman, Nurul; Warti , Erlis (Delta: Jurnal Ilmiah Pendidikan Matematika, 2025)
Students often struggle to understand trigonometry due to its abstract nature and the need for strong visualization skills. This study aims to develop a web-based interactive learning media on trigonometry to enhance students’ mathematical reasoning ability in Grade X at Madrasah Aliyah Nurul Huda. The research employed the ADDIE development model, consisting of analysis, design, development, implementation, and evaluation stages. Validation results indicated that the developed media is highly feasible, with a score of 97% (very feasible) from subject matter and language experts, and 84% (feasible) from media experts. The product features concise content, interactive simulations for better visualization, evaluation exercises, and wordwall-based games accessible via smartphones or computers. Effectiveness tests showed an improvement in students’ reasoning skills with an average N-gain of 0.41 in small-scale trials and 0.54 in field trials (moderate category), along with a significant difference between pre-test and post-test scores (sig. 0.001 < 0.05). The findings imply that web-based interactive media can serve as an effective alternative to improve the quality of mathematics learning, especially in trigonometry